Integrating research into the practicum: inquiring into inquiry-based professional development in post-Bologna Initial Teacher Education in Portugal - Flores, Maria Assunção (2016)
One of the critical issues in ITE is the role of research in professional learning. Inquiry-based teacher education has long been advocated, but it is far from representing a common approach and faces various challenges. This chapter discusses the role of inquiry in the practicum of post-Bologna ITE master programmes in Portugal by drawing on the case of the practicum model implemented at the University of Minho (Braga, Portugal) since 2009/10. It presents data collected through a survey questionnaire and focus group interviews to practicum participants, and the analysis of a corpus of student teachers’ practicum reports. The study shows that the emergence of an inquiry-based culture in the practicum is both innovative and controversial, incorporating tensions as regards visions of teacher education, as well as (in)coherences between curriculum rhetoric and implementation. Findings point out the need to develop a scholarship of teacher education whereby ITE programmes are investigated and improved on the basis negotiated understandings.